2017
DOI: 10.1038/srep41561
|View full text |Cite
|
Sign up to set email alerts
|

Joint genome-wide association and transcriptome sequencing reveals a complex polygenic network underlying hypocotyl elongation in rapeseed (Brassica napus L.)

Abstract: Hypocotyl elongation is considered an important typical seedling trait contributing directly to an increase in and stabilization of the yield in Brassica napus, but its molecular genetic mechanism is poorly understood. In the present study, hypocotyl lengths of 210 lines were measured in an illuminated culture room. A genome-wide association study (GWAS) was performed with 23,435 single nucleotide polymorphisms (SNPs) for hypocotyl length. Three lines with long hypocotyl length and three lines with short hypoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
(74 reference statements)
2
6
0
Order By: Relevance
“…In general, we found that biomass gradually increased as storage depth and duration were extended regardless of the packaging method used. Furthermore, biomass and hypocotyl length showed similar variation with storage time, which is similar to the results reported by (Luo et al, 2017). Therefore, the lengthening of the hypocotyl with storage depth and duration may explain the observed increase in biomass accumulation.…”
Section: Germination Processsupporting
confidence: 89%
See 2 more Smart Citations
“…In general, we found that biomass gradually increased as storage depth and duration were extended regardless of the packaging method used. Furthermore, biomass and hypocotyl length showed similar variation with storage time, which is similar to the results reported by (Luo et al, 2017). Therefore, the lengthening of the hypocotyl with storage depth and duration may explain the observed increase in biomass accumulation.…”
Section: Germination Processsupporting
confidence: 89%
“…The elongation of the hypocotyl is a crucial feature of the seedling stage; with better development of the seedling, a satisfactory yield can be obtained (Luo et al, 2017). In the present study, the maximum hypocotyl length usually appeared after more extended storage periods for seeds in both envelopes and sealed packages.…”
Section: Germination Processsupporting
confidence: 48%
See 1 more Smart Citation
“…Enhanced hypocotyl elongation is like enhanced epicotyl (shoot) elongation before winter presumably related to reduced frost tolerance. Hypocotyl elongation has not been measured in the present studies, but in a genome wide association study Luo et al (2017) suggested candidate gene BnaC07g46770D among others as a negative regulator of hypocotyl elongation and of flowering time. In the present study, no significant QTL for shoot elongation was detected on C07 in the autumn and in the spring-sown environment.…”
Section: Discussionmentioning
confidence: 60%
“…Circadian clocks fine-tune physiology and behaviour to match the environmental day/night cycle [39,40]. The plant circadian clock generates daily and even seasonal rhythms in an orderly succession of physiological processes including stomatal opening, leaf movement, hypocotyl elongation, photosynthesis and carbon metabolism, resistance to abiotic and biotic stresses, and flowering time [15,33,[41][42][43][44][45]. Expression analysis of critical genes helped to dissect the genetic basis of important traits, such as floral in hickory [46] and Persian walnut [47].…”
Section: Detection Of Circadian Genes For the Flower Bud Developmentmentioning
confidence: 99%